Functional Properties of Protein Hydrolysates from Skipjack Tuna Byproducts Using Response Surface Methodology - Prasetyo, Dwi Yanuar Budi; Agustini, Tri Winarni; Anjani, Gemala; Riyadi, Putut Har (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2024)
Protein hydrolysates from skipjack tuna by-products are rich in protein and excellent in functional properties, making them a valuable source of nutrients for humans. This research sought to determine the optimal pH, temperature, and hydrolysis time for producing protein hydrolysates from skipjack tuna byproducts (PHST) using Response Surface Methodology (RSM). A total of 20 g of PHST was prepared from frames and trimmings, samples were hydrolyzed under the following conditions: pH of 6 (P1) and 7 (P2), temperatures of 50°C (S1), 60°C (S2), and 70°C (S3), and hydrolysis times of 90 minutes (T1), 180 minutes (T2), and 270 minutes (T3). The hydrolysis process was terminated by inactivating the enzyme at 80°C for 30 minutes. The filtrate was ready for further analysis in the laboratory. Data and design experiments were analyzed using Box-Behnken Design (BBD) with the Design-Expert (DX) 13® software (Stat-Ease Inc. Minneapolis) to determine the optimum conditions for higher PHST production. A quadratic model was developed to predict the production of PHST. The RSM recommendation was to perform hydrolysis at pH 6.386 and a temperature of 61.190°C for a hydrolysis time of 228.540 minutes to result in a desirability of 0.906 in producing PHST with 85.680% DH, a protein solubility of 51.538%, and a viscosity of 3.587%. The study results showed that PHST can be used as a promising food ingredient and protein source in the food system.